Paul's Online Notes
Home / Calculus I / Derivatives / The Definition of the Derivative
Show Mobile Notice Show All Notes Hide All Notes
Mobile Notice
You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.

### Section 3.1 : The Definition of the Derivative

3. Use the definition of the derivative to find the derivative of,

$g\left( x \right) = {x^2}$

Show All Steps Hide All Steps

Start Solution

First we need to plug the function into the definition of the derivative.

$g'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \frac{{g\left( {x + h} \right) - g\left( x \right)}}{h} = \mathop {\lim }\limits_{h \to 0} \frac{{{{\left( {x + h} \right)}^2} - {x^2}}}{h}$

Make sure that you properly evaluate the first function evaluation. This is one of the more common errors that students make with these problems.

Show Step 2

Now all that we need to do is some quick algebra and we’ll be done.

$g'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \frac{{{x^2} + 2xh + {h^2} - {x^2}}}{h} = \mathop {\lim }\limits_{h \to 0} \frac{{h\left( {2x + h} \right)}}{h} = \mathop {\lim }\limits_{h \to 0} \left( {2x + h} \right) = 2x$

The derivative for this function is then,

$\require{bbox} \bbox[2pt,border:1px solid black]{{g'\left( x \right) = 2x}}$